In Vitro Validation of a Technique for Assessment of Canine and Feline Elbow Joint Collateral Ligament Integrity and Description of a New Method for Collateral Ligament Prosthetic Replacement - FARRELL, MICHAEL; DRAFFAN, DAVINIA; GEMMILL, TOBY; MELLOR, DOMINIC; CARMICHAEL, STUART (Veterinary surgery, 2007)
To assess the ability of an operator to differentiate intact from transected canine and feline elbow joint collateral ligaments (CL) using a reported manipulative test (Campbell's test) and to determine the potential for elbow joint luxation in canine and feline elbows with intact, transected, and surgically stabilized CL. In vitro biomechanical study. Canine (n=6) and feline cadavers (n=3). Thoracic limb specimens were mounted on a custom-built jig with the elbows and carpi fixed in 90° of flexion. Angles of pronation and supination were recorded after applying rotational forces to the manus. Attempts were made to manually luxate each elbow with intact CL. Constructs were re-evaluated after sequential sectioning of the medial (MCL) and lateral (LCL) collateral ligaments and after insertion of a new CL prosthesis. Mean (±SD) angles of rotation in dogs increased from 27.3±8° (range, 16.7-41.3°) in pronation to 58.9±9.2° (range, 38-88.3°) after sectioning the MCL and from 45.5±10.8° (range, 30.7-67.3°) in supination to 68.9±17.2° (range, 45-94°) after sectioning the LCL. Angles of pronation and supination were subject to significant interanimal variability, with a strong correlation between increasing animal weight and smaller angles of rotation. Elbow luxation in dogs was not possible unless at least the LCL was transected. In cats, mean angles of rotation increased from 49.8±14.9° (range, 30.7-70°) in pronation to 99.1±17.6° (range, 79-111.7°) after sectioning the MCL and from 128.7±18.8° (range, 108.3-151.7°) in supination to 166.7±13.1° (range, 157.3-181.7°) after sectioning the LCL. Luxation in cats was not possible unless both CL were cut. Use of the ligament prosthesis without primary CL repair reliably prevented reluxation in all canine and feline elbows. Campbell's test allowed reliable differentiation of intact, transected and surgically stabilized canine and feline elbow joint CL in a cadaveric model. Luxation could not be performed by application of rotational forces to specimens with intact CL. Clinical examination findings, specifically Campbell's test, can be used to determine elbow CL integrity in dogs and cats. The contralateral elbow should be used as a control, because of interanimal variability in angles of rotation.